Quarter-Life Crisis (QLC) dalam Budaya Indonesia: Analisis Konstruksi Sosial Peter Berger - Muhammad Zidan Abadi (Journal of Education and Social Culture, 2026)
Quarter-Life Crisis (QLC) is a psychosocial phenomenon that is increasingly prominent among young Indonesians, especially in a cultural context laden with social expectations. This study aims to analyse QLC through the perspective of Peter L. Berger's social construction theory, highlighting how social norms, family pressure, and media representations shape individuals' subjective experiences. The research method used is qualitative analysis based on literature review, with an emphasis on the processes of habitualisation, objectification, and internalisation in constructing social reality related to QLC. The results of the analysis show that QLC arises as a consequence of the tension between institutionalised social expectations and the diverse actual conditions of individuals. Norms internalised within individuals often cause psychological pressure in the form of anxiety and identity crises. This study concludes that QLC in Indonesia is a socially constructed reality, thus requiring a more inclusive and adaptive socio-cultural approach to help the younger generation deal with this phase in a healthier and more reflective manner.